Pembagian Warisan terhadap Anak Perempuan di Mandailing Natal - Nindi Aliska Nasution (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to determine the implementation of property inheritance to daughters in Tanjung Mompang Panyabungan Utara Mandailing Natal and the factors that cause people to choose the way in the distribution of inheritance. This article uses a juridical-empirical approach. The results of this research shows that the distribution of inheritance done traditionally due to the lack of public awareness about Islamic civil law particularly about inheritance. It becomes the most fundamental factors causing disputes and injustice among family members because the inheritance were distributed not in accordance with Islamic law. Religious and education factors are two common factors that determine the distribution of inheritance. Low understanding of Islamic law and inheritance knowledge are the cause of this case.